1985
DOI: 10.1111/1523-1747.ep12276482
|View full text |Cite
|
Sign up to set email alerts
|

A Porphyria Cutanea Tarda-like Distribution Pattern of Porphyrins in Plasma, Hemodialysate, Hemofiltrate, and Urine of Patients on Chronic Hemodialysis

Abstract: The porphyrin investigations of plasma, dialysate, hemofiltrate, and urine in 50 chronic renal patients without bullae undergoing hemodialysis imply that a hyperporphyria exists. All 50 dialysis patients without blisters had significantly elevated plasma porphyrins with a mean of 27.4 micrograms/liter (SD: 10.0). Normal values were established in 51 nonporphyric ambulatory patients with normal renal function. The mean plasma porphyrin content in this group was 10.6 micrograms/liter (SD: 1.7). Porphyrin values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Seubert et al [14] found that uroporphyrin I was the main isomer in patients with CRF, unlike Day and Eales [5] who found mainly isomer III. We could only detect uroporphyrin I and not uroporphyrin III in the plasma of our patients.…”
Section: Discussionmentioning
confidence: 90%
“…Seubert et al [14] found that uroporphyrin I was the main isomer in patients with CRF, unlike Day and Eales [5] who found mainly isomer III. We could only detect uroporphyrin I and not uroporphyrin III in the plasma of our patients.…”
Section: Discussionmentioning
confidence: 90%
“…Only small amounts of intermediates are lost from the pathway and excreted either unchanged or after oxidation to porphyrins, the (2), PBG-deaminase (3). uroporphyrinogen-Hl synthase (4), uroporphyrinogen decarboxylase (5), coproporphyrinogen oxidase (6), protoporphyrinogen oxidase (7) and ferrochelatase (8). In normal circumstances, less than 1% 0/ hydroxymethylbilane is cyclized non-enzymatically to uroporphyrinogen I.…”
Section: Biosynthesis and Metabolism Of Haem Precursorsmentioning
confidence: 99%
“…Nalidixic acid [5]dyazide [18]tetracycline [14], chlortalidone [14]bumetanide [14], amiodarone [14], etretinate [14], isotretinoin [19], pyridoxine [14], cyclosporin [20]5-fluorouracil [21]hemodialysis [1, 4, 9, 10]or peritoneal dialysis [9, 10, 15]alone have also been reported to induce PP [14, 15]. Drug-induced PP is interpreted by some authors as a phototoxic-mediated disorder [12, 14].…”
Section: Discussionmentioning
confidence: 99%
“…This entity is characterized by the sudden occurrence of blisters in the UV-exposed skin and an increased skin fragility [2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13]. The etiology of the disease is not yet clarified.…”
Section: Introductionmentioning
confidence: 99%